Career counseling meets motivational interviewing: A sequential analysis of dynamic counselor-client interactions - Klonek, Florian; Wunderlich, E.; Spurk, D.; Kauffeld, S. (Academic Press, 2016)
Motivational Interviewing (MI) is a client-centered communication style with the aim to resolve client ambivalence within a change-related counseling. Its potential benefit for career counseling has been discussed by several scholars but no empirical research has investigated MI in this context so far. The current study used process measures from MI to investigate dynamic interactions within a career counseling intervention. Overall, we analyzed two videotaped sessions of 14 unique counselor-client dyads. Verbal behavior of counselors and clients were coded with two observational coding schemes from MI (one for counselors and one for clients, respectively). Behavior profiles of counselors were compared with benchmarks of good MI. Furthermore, client verbal ambivalence was compared between sessions. Finally, we conducted lag sequential analyses to analyze temporal dynamics between counselor behavior and immediate client verbal responses across N = 6883 behavioral events. Our results showed, first, behavior profiles of career counselors did significantly differ from recommended counseling benchmarks of good MI practice. Second, as assumed on the basis of past studies, client ambivalence decreased across sessions. Third, MI consistent counselor behaviors showed a positive sequential association with client positive career talk, whereas MI inconsistent counselor behaviors showed the reverse pattern. Our results suggest that counseling behaviors recommended from MI are facilitating career interventions. We discuss how trainings in MI could amend career counseling interventions and provide ethical implications when integrating MI into career counseling programs.